The Abode of Hellenic λόγος: Appreciations on the Genesis and Conformation of the Metaphysical Project - Martínez Ortega, Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
The following essay has as its main objective the investigation on the genesis and conformation of the term «λόγος» at the beginning of the tradition of western metaphysics. The extention, evolution and variance of the use of the term in Greek literature and the thought in its origins show the connection and roots of the Greek metaphysical project with the Hellenic world view, the theogonic vision, and poetic thinking.